2015
DOI: 10.3390/f6051628
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Trembling Aspen and White Spruce Wood Quality Grown in Mixed and Single Species Stands in the Boreal Mixedwood Forest

Abstract: Abstract:The Canadian boreal forest is largely represented by mixed wood forests of white spruce (Picea glauca (Moench) Voss) and trembling aspen (Populus tremuloides Michx). In this study, a total of 300 trees originating from three sites composed of trembling aspen and white spruce with varying compositions were investigated for wood quality traits: one site was composed mainly of aspen, one mainly of spruce and a third was a mixed site. Four wood quality traits were examined: wood density, microfibril angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 46 publications
2
6
1
Order By: Relevance
“…Previous study has shown that there was no effect of mixed vs pure competition having an effect on wood density (De Araujo et al 2015)…”
Section: Wood Attribute Description Economic Value History Densitymentioning
confidence: 92%
See 4 more Smart Citations
“…Previous study has shown that there was no effect of mixed vs pure competition having an effect on wood density (De Araujo et al 2015)…”
Section: Wood Attribute Description Economic Value History Densitymentioning
confidence: 92%
“…Within mixed forest plantations in Eastern Quebec, distance independent indices have successfully quantified the competition effect on basal area increment growth in planted white spruce, while distance-independent indices worked best for ingrown or non-planted species (Bérubé-Deschênes 2017). In an analysis of permanent sample plots that included pure and mixed stands of aspen and white spruce of varying age in Central Alberta, wood density and carbohydrate content was found to be consistent across sites, while MFA was lower within aspen sampled in pure stands and fibre characteristics were higher in the pure site for both species (De Araujo et al 2015). Previous studies have been limited due to sampling uneven age stands with inconsistent measures of treatment density.…”
Section: Competition In the Mixedwoodmentioning
confidence: 94%
See 3 more Smart Citations